Non-Atherosclerosis Acute Coronary Syndrome: A Review Article - Afifah, Yuri; Rosandy, Kharima Ogit; Satrijo, Budi (Universitas Brawijaya, 2024)
Non-atherosclerotic acute coronary syndrome (ACS) refers to a group of conditions that cause myocardial damage and clinical symptoms like traditional ACS but are not primarily caused by coronary artery plaque rupture or obstruction. This abstract provides an overview of the etiology, clinical presentation, diagnosis, and management of non-atherosclerotic ACS. Several etiologies can lead to non-atherosclerotic ACS, including coronary artery vasospasm, connective tissue disorders, stress-induced cardiomyopathy (Takotsubo syndrome), and vasculitis. The clinical presentation can mimic traditional ACS, with chest pain being the most common symptom. Diagnostic tools such as electrocardiography (ECG), laboratory biomarkers, echocardiography, coronary angiography, cardiac magnetic resonance imaging (MRI), and nuclear imaging play a crucial role in distinguishing non-atherosclerotic ACS from traditional ACS. Treatment strategies for non-atherosclerotic ACS are often based on expert consensus and clinical experience due to the lack of specific guidelines. Management approaches depend on the underlying etiology and may include pharmacological therapy, invasive interventions such as percutaneous coronary intervention (PCI) or surgery, and risk factor modification. Prompt diagnosis and appropriate management are crucial for improving patient outcomes. Further research and prospective studies are needed to enhance our understanding of non-atherosclerotic ACS and optimize its management.